ANALISIS FAKTOR PENENTU PERFORMA PERUSAHAAN MANUFAKTUR YANG TERCATAT BEI TAHUN 2017-2020 - Sabdaputra, Ray; Rasyid, Rosmita (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
The purpose of this research is to obtain empirical evidence on the influence of leverage, asset structure, liquidity, company size, non-debt tax shields, and managerial ownership of the performance of manufacturing companies listed on the Indonesia Stock Exchange for the period 2017-2020. Sampling in this study used purposive sampling methods and obtained 48 samples of manufacturing companies listed on the Indonesia Stock Exchange for the period 2017-2020. The study used the Eviews 12 and Microsoft Excel 2016 software programs to manage data. The results of this study showed that leverage and asset structure had a negative influence on the company's performance, liquidity and non-debt tax shields had no negative influence on the company's performance while the size of the company and managerial ownership did not have a positive influence on the company's performance. The implication of this research is the need to reduce the use of debt to minimize the interest expense of the debt which will increase the company's profit so as to improve the company's performance which will provide good information for investors.